Analytical and numerical approach of an End Notched Flexure test configuration with an inserted roller for promoting mixed mode I/II. (July 2015) - Boyano, A.; Mollón, V.; Bonhomme, J.; De Gracia, J.; Arrese, A.; Mujika, F.
Highlights: A new test configuration for mixed mode I/II for interlaminar fracture. Reasonable agreement between analytical and numerical results. Wide range of mode mixities can be obtained varying the roller radius or position. Energy released rate is obtained by complementary strain energy. Abstract: A test configuration for studying mixed-mode is analyzed analytically and numerically. It is based on the End Notched Flexure test, inserting a roller in the cracked part in order to promote mixed mode I/II. The analytical approach includes the calculation of the force exerted by the roller, the midpoint displacement, the compliance of the test, and the relative displacement of both arms of the crack. Moreover, the energy release rate is determined based on the complementary strain energy. With respect to numerical analysis, the two-step extension procedure is used for determining energy release rates in mode I and mode II. Comparison between analytical and numerical results has been carried out in order to check the suitability of the test method.